Effect of providing awareness regarding the text neck syndrome in young adults - Kulkarni, Manjiri A.; Lakhwani, Namrata; Prajapati, Nisha; Prajapati, Dhruvisha; Modi, Bhumi; Muni, Pooja (International Journal Of Community Medicine And Public Health, 2022)
Background: Electronic gadgets are indispensable part of our life which has reached every doorstep across the globe. With advancing age the use of mobile phones have drastically increased and people spend long hours on their gadgets which has led to several musculoskeletal problems. Constant head down posture and improper alignment of head and neck attained during usage leads to permanent damage in cervical spine such as flattening of spinal curve, early onset of arthritis, spine degeneration, disc compression and herniation. The term text neck can be described as repetitive stress injury and pain sustained from excessive use of handheld devices. Lack of awareness and negligence amongst the young population text neck syndrome can result in inflammation of neck ligaments, muscle and nerves leading to permanent changes. This study aims to find out the effects of providing awareness regarding text neck syndrome and it preventive measures while using hand held device. Methods: 218 young healthy adults were pre given a pre-test regarding the awareness of text neck syndrome, later they were given an information brochure. Following this, the participants were given a post-test to check the effect of providing information regarding Text neck syndrome. Results: Results of the study revealed that there was significant improvement in post test score as compared to pre-test using paired t test (p value >0.05). Conclusions: There was lack of awareness regarding the syndrome and its preventive measures, after appropriate providing information, awareness were established in the young adult population.